Calappa exanthematosa Alcock & Anderson, 1894, as a valid species of box crab from the Indian Ocean (Crustacea: Decapoda: Calappidae) - Ng, Peter K. L.; Lai, Joelle C. Y.; Ghotbeddin, Negar; Safaie, Mohsen (Zootaxa, 2011)
The box crab Calappa exanthematosa Alcock & Anderson, 1894, originally described from the Bay of Bengal, has been synonymised under C. japonica Ortmann, 1892 (type locality Japan), since 1937. Comparisons of specimens from the Gulf of Oman and India reveal consistent differences in the live colour of material from the rest of the Indo-West Pacific region, carapace (general form, shape of lateral teeth, position of longitudinal gastro-cardiac grooves, structures of posterior region), pterygostomian lobe, chela, male abdominal somite 6, male telson and G1. Calappa exanthematosa is here recognised as a distinct species, redescribed, and illustrated.